2004
DOI: 10.1016/j.nuclphysb.2004.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Long range disorder and Anderson transition in systems with chiral symmetry

Abstract: We study the spectral properties of a chiral random banded matrix (chRBM) with elements decaying as a power-law Hij ∼ |i−j| −α . This model is equivalent to a chiral 1D Anderson Hamiltonian with long range power-law hopping. In the weak disorder limit we obtain explicit nonperturbative analytical results for the density of states (DoS) and the two-level correlation function (TLCF) by mapping the chRBM onto a nonlinear σ model. We also put forward, by exploiting the relation between the chRBM at α = 1 and a gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…This seems to suggest that Anderson localization and the chiral phase transition cannot be so intimately related. However, in disordered systems with chiral symmetry (or any other additional discrete symmetry) the spectral density is already sensitive to the strength of disorder [30,31] so it may still play the role of an order parameter for the transition. Additionally the fluctuations of the order parameter are related to density-density correlations which are sensitive to localization effects even in systems with no chiral symmetry.…”
Section: Additional Discussion On Localization and Chiral Restoramentioning
confidence: 99%
“…This seems to suggest that Anderson localization and the chiral phase transition cannot be so intimately related. However, in disordered systems with chiral symmetry (or any other additional discrete symmetry) the spectral density is already sensitive to the strength of disorder [30,31] so it may still play the role of an order parameter for the transition. Additionally the fluctuations of the order parameter are related to density-density correlations which are sensitive to localization effects even in systems with no chiral symmetry.…”
Section: Additional Discussion On Localization and Chiral Restoramentioning
confidence: 99%
“…A practical problem of using the microscopic level density ρ(x) = K chi a (x, x) for fitting the Dirac spectrum is that ρ(x) becomes rather structureless at a finite deformation parameter a (see Fig.8 below) [49]. On the other hand, the level number variance (an integral transform of the twolevel correlation function −K chi a (x, x ) 2 ) for large x is sensitive to the parameter a, but one would need extremely large lattices for the window at the origin containing dozens of eigenvalues to be uniformly fitted with a single parameter a.…”
Section: Pos(lattice 2013)018mentioning
confidence: 99%
“…Such an example can be found in Ref. [16]. The generalized random matrix model was used there and it was found that the quantity ⌬ is different from our result.…”
Section: Discussionmentioning
confidence: 56%
“…Using a chiral symmetric random matrix model we derived the nonlinear models (16) and (19). We demonstrated that they are equivalent to related chiral symmetric models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation